2018
DOI: 10.1007/s10389-018-0917-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of preparedness of healthcare student volunteers against Middle East respiratory syndrome coronavirus (MERS-CoV) in Makkah, Saudi Arabia: a cross-sectional study

Abstract: AimTo assess the knowledge and attitude of senior medical, dental, nursing and pharmacy students toward Middle East respiratory syndrome-corona virus (MERS-CoV) in Saudi Arabia.Subjects and methodsA cross-sectional survey using a 21-item questionnaire was conducted for a 3-month period from November 2015–January 2016 in Makkah, Saudi Arabia. The questionnaire was designed to evaluate students’ understanding and perception of MERS-CoV. An ANOVA test was used to determine the association of study discipline and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 18 publications
5
84
2
2
Order By: Relevance
“…The relatively low percentage of participants with a good knowledge level in this study is in line with ndings of a study conducted among health care workers which reported that Knowledge and perceptions of COVID-19 varied across different categories of health care workers but in general the participants had a poor knowledge level (Bhagavathula et al 2020a). Nevertheless, the percentage of participants with a good knowledge level is lower when compared to studies conducted among different segments of the society against MERS (Kharma et al 2015;Elrggal et al 2018) and against COVID 19 (Zhong et al 2020;Wolf et al 2020;Zhang et al 2020a) where the participants have claimed good knowledge regarding transmission, symptoms and treatment of COVID-19.…”
Section: Discussionmentioning
confidence: 85%
“…The relatively low percentage of participants with a good knowledge level in this study is in line with ndings of a study conducted among health care workers which reported that Knowledge and perceptions of COVID-19 varied across different categories of health care workers but in general the participants had a poor knowledge level (Bhagavathula et al 2020a). Nevertheless, the percentage of participants with a good knowledge level is lower when compared to studies conducted among different segments of the society against MERS (Kharma et al 2015;Elrggal et al 2018) and against COVID 19 (Zhong et al 2020;Wolf et al 2020;Zhang et al 2020a) where the participants have claimed good knowledge regarding transmission, symptoms and treatment of COVID-19.…”
Section: Discussionmentioning
confidence: 85%
“…For attitudes about pandemics, worry/fear/helplessness about pandemic (13, 14, 22, 28, 31, 33, 49, 51, 52, 60, 61, 63, 65, 68, 72, 76-78, 81, 83, 84), confidence in governments' ability to manage pandemic (13,23,28,30,33,41,61,63,65,68,70,77,78,82) and perceived severity of infection as a public health problem (13,29,39,41,44,45,59,65,70,72) was most commonly assessed. (Table 3) For practices in pandemics, behaviours related to mask utilization (14,16,23,26,28,30,32,33,35,38,40,48,59,61,63,65,70,73,80,82,(84)(85)…”
Section: Themes Identified From Items Used In Health Literacy Questiomentioning
confidence: 99%
“…Given that this virus is most commonly spread by respiratory droplets from infected individuals, this is not a surprising finding. While the majority of participants in a recent Saudi Arabian study among medical students were aware that infection prevention was ideally through wearing face masks and public information, 53% of participants were unaware of infection control isolation policies in their hospitals, if an outbreak arose [34]. Furthermore, nosocomial transmission is made worse by the presence of MERS-CoV "superspreaders", who transmit the disease at a significantly higher rate than the average host [35].…”
Section: Mers-cov Ecology and Transmissionmentioning
confidence: 99%
“…This included where to seek medical attention and protective measures individuals could take to protect themselves from infection, such as face masks. In the case of MERS, there is a belief that lack of knowledge among medical staff and affected communities could be a risk factor for disease containment [34]. With a combination of hospital and community outbreaks, many have suggested that stronger implementation of proper decontamination procedures could reduce outbreak severity and length [8,42].…”
Section: Introduction To the 2013 Saudi Arabian And 2015 South Koreanmentioning
confidence: 99%